Role and Status of Women in Islam - Alikunju, Haji K P (Journal of Dharma, 1986)
Islam envisages that the men and women have equal role in defending the faith. The holy Quran says as follows: The believers men and women are protectors, one of another : they enjoin what is just, and forbid what is evil . they observe regular prayers, practise regular charity, and obey God and His Apostle. "In them will God pour His mercy: for God is exalted in power, Wise" "God hath promised to Believers, men and Women, gardens under which rivers flow, To dwell therein, and beautiful mansions in the gardens of everlasting bliss. But the greatest bliss is the good pleasure of God • That is the supreme felicity". (Sura paras 71 and 72).